2018
DOI: 10.1111/1742-6723.12989
|View full text |Cite
|
Sign up to set email alerts
|

Review article: Isolated proximal tibiofibular joint dislocation

Abstract: Proximal tibiofibular joint (PTFJ) dislocations are relatively rare injuries and this paper provides an up-to-date review and practical management approach for the assessment and management of these cases. Isolated PTFJ dislocations are a rare injury, accounting for less than 1% of all knee injuries. Thus, there does not appear to be a clear consensus on definitive management and post-reduction care in the literature. This paper provides a review of the literature, anatomical analysis of the PTFJ in the disloc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 30 publications
0
15
0
Order By: Relevance
“…Although there have been reports of dislocation of the hip, patella, shoulder, elbow joints, etc, in patients with EDS,1–3 a case of dislocation of the PTFJ associated with EDS has never been reported. Traumatic PTFJ dislocation in adulthood, although rare,13 provides little useful information about the effects of PTFJ dislocation in skeletally immature knees on bony growth and/or bony deformities. From the present case, we found that the dislocation of the fibula, which acts as a supporting strut for the posterolateral part of the tibial condyle,14 15 caused dysplasia of the posterolateral tibia, resulting in valgus knee alignment.…”
Section: Discussionmentioning
confidence: 99%
“…Although there have been reports of dislocation of the hip, patella, shoulder, elbow joints, etc, in patients with EDS,1–3 a case of dislocation of the PTFJ associated with EDS has never been reported. Traumatic PTFJ dislocation in adulthood, although rare,13 provides little useful information about the effects of PTFJ dislocation in skeletally immature knees on bony growth and/or bony deformities. From the present case, we found that the dislocation of the fibula, which acts as a supporting strut for the posterolateral part of the tibial condyle,14 15 caused dysplasia of the posterolateral tibia, resulting in valgus knee alignment.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the most common fracture morphology associated with proximal tibiofibular injury was a tibial shaft fracture (Figure 2 ) (68.75%), which is consistent with previous studies. 10 , 21 Of the many case reports published on this topic, 9 10 11 12 13 14 15 16 17 18 19 20 21 this systematic review was only able to identify three larger case series that have published the epidemiology of these injuries. Herzog et al 2 published a similarly high rate of open fracture (76.7%) and peroneal nerve palsy (36%) with their series of 30 proximal tibiofibular injuries; however, their rate of vascular injury was lower at 6.7%.…”
Section: Discussionmentioning
confidence: 99%
“… 3 4 5 6 7 8 There is overall a paucity of literature on traumatic dislocations of the proximal tibiofibular joint, although a few small case studies have been reported. 9 10 11 12 13 14 15 16 17 18 19 20 21 There is similarly no systematic review of the literature on this topic.…”
mentioning
confidence: 99%
“…When a lesion is suspected, the image of choice is computed tomography (CT) [1]. It has been found that on some occasions DPTJ can be spontaneous, but if this is not the case, the closed reduction under sedation has been proposed as a conservative treatment, and in some cases of late diagnosis, internal fixation or arthrodesis has been proposed as a solution, although the reports on this are scarce [4][5][6].…”
Section: Introductionmentioning
confidence: 99%